THE EXPLOITATION OF PORTAL DIDTECH AS SUPPORT FOR PRESENT AND FUTURE TEACHERS - BRECKA, Peter (Trends in education, 2008)
The article describes the need of creation of DIDTECH portal (as a part of VEGA project solution). The main aim of the portal is to help the present and future teachers (and students as well) on the area of technical parameters and function principles of the newest didactical techniques. The portal should help by the implementation of the mentioned technique to the educational process.
Keywords: portal; didactical technique; e-learning; e-course